2008
DOI: 10.1159/000150599
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Symptoms and the Quality of Life in Patients on Hemodialysis for End-Stage Renal Disease

Abstract: Background: End-stage renal disease (ESRD) is a progressive, debilitating, chronic illness requiring nursing and medical interventions. The goal of this study was to explore the level of depression experienced by patients receiving hemodialysis (n = 146), and to compare the symptoms with the quality of life (QoL) between patients that were depressed and those that were not depressed. Methods: For this descriptive, cross-sectional survey, participants aged 18 and above were recruited from three different region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 33 publications
3
49
0
12
Order By: Relevance
“…The severity of depressive disorder is considered moderate for scores ranging from 10 to 14, moderately severe for scores of 15 to 19, and severe for scores of 20 to 27. The PHQ-9 has been used to assess depression in patients with ESRD and those with CKD (25)(26)(27). In patients on hemodialysis, scores Ͼ9 are 92% sensitive and specific for a diagnosis of depressive disorder (25).…”
Section: Assessment Of Symptoms Depression and Quality Of Lifementioning
confidence: 99%
“…The severity of depressive disorder is considered moderate for scores ranging from 10 to 14, moderately severe for scores of 15 to 19, and severe for scores of 20 to 27. The PHQ-9 has been used to assess depression in patients with ESRD and those with CKD (25)(26)(27). In patients on hemodialysis, scores Ͼ9 are 92% sensitive and specific for a diagnosis of depressive disorder (25).…”
Section: Assessment Of Symptoms Depression and Quality Of Lifementioning
confidence: 99%
“…The QoL domains include physical, psychological, and social functioning and general satisfaction with life (Tsay & Healstead, 2002). Once patients with ESRD start to receive HD, they must face the chronic stress related to restrictions on their time, the economical and vocational costs related to treatment, functional limitations, dietary constraints, and possible adverse effects of medications (Son et al, 2009). Numerous studies have demonstrated that these patients have a lower QoL than that of healthy populations (Kao et al, 2009;Perlman et al, 2005;Wolcott et al, 1988).…”
Section: Decreased Quality Of Life (Qol)mentioning
confidence: 99%
“…More than 90% of these patients were started on hemodialysis (HD), while only 8.5% began RRT with peritoneal dialysis (PD) (Kimmel & Peterson, 2005). In Korea, the number of dialysis centers and machines has continuously increased, and 62.1% of patients receiving RRT were being treated with HD (Son et al, 2009). An international comparison showed that Taiwan has the greatest incidence and second-greatest prevalence of ESRD (Kuo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…44 The etiology of depressive disorders in CKD patients is multiple, including psychological, physical and socioeconomic state. Leptin, adiponectin, neuropeptide Y, ghrelin and resistin were reported to be involved in pathophysiology of depressive disorders among subjects with normal kidney function.…”
Section: Discussionmentioning
confidence: 99%